BATASAN DAN MEKANISME PENERAPAN SANKSI PIDANA PERPAJAKAN DI INDONESIA DALAM PERSPEKTIF ASAS ULTIMUM REMEDIUM - Safitri, Eka Ayu; Damayanti, Ratih; Sulistiyono, Tri (Jurnal Hukum Statuta, 2025)
This study examines the limitations and mechanisms of the application of criminal sanctions against taxpayers who violate tax provisions in Indonesia, and evaluates the application of the ultimum remedium principle as the principle of "criminal sanctions as a last resort." Using a qualitative legal-normative approach with a descriptive-analytical method, data was collected through a documentation study of primary sources (Law 7/2021 in conjunction with Law 6/2023 concerning KUP, KUHAP, KUHP) and secondary sources (scientific journals 2020–2025, textbooks, DGT guidelines). Normative-dogmatic analysis reveals that the KUP Law explicitly separates administrative and criminal sanctions without setting a minimum loss threshold for criminal prosecution, so that tax officials tend to use criminal sanctions only for high-value cases. The legal-theoretical study explains that the ultimum remedium principle is accommodated through provisions such as Article 8 paragraph (3) and Article 44B of the KUP Law, but in practice it still encounters inconsistencies and broad discretion. Synthesis of findings indicates the need for quantitative guidelines for loss thresholds, reintegration of the “first-time offender” protocol, and harmonization of the Criminal Procedure Code with the principle of criminal subsidiarity. These recommendations are expected to strengthen the implementation of the ultimum remedium principle, ensuring that criminal sanctions are truly the last resort in enforcing fair and proportional tax law. Keywords: Taxation; Ultimum Remedium; Criminal Sanctions; KUP Law; Criminal Law